(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This article considers it important to improve the technologies for forming gender culture among schoolchildren, as well as the formation of gender culture in students. This requires the development of effective mechanisms for introducing gender culture into the education system and managing it. It is urgent to consider the problems of forming gender culture in students and take measures to form them.